Representasi Karakter Patriotik pada Novel Tanah Para Bandit Karya Tere Liye Menurut Perspektif Louis J. Halle - Kadaryati Kadaryati; Ridho Bayu Saputro; Jannata Annisa Azizah; Najwatul Auliah; Nur Baeti (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2024)
This study aims to describe the representation of patriotic character in Tere Liye’s novel Tanah Para Bandit using Louis J. Halle’s theory, which includes four main dimensions: loyalty, sacrifice, civic responsibility, and moral integrity. The research employed a qualitative descriptive approach with content analysis techniques applied to narrative excerpts, dialogues, and character actions. The results show that patriotic values are strongly reflected in the main character, who is portrayed as principled, self-sacrificing, and highly aware of the nation’s welfare. The element of loyalty appears in the protagonist’s commitment to social justice. Sacrifice is evident in the courage to face danger for the sake of the oppressed. Civic responsibility is expressed through the character’s moral conduct and social solidarity, while moral integrity emerges in the unwavering stance for truth and justice. In conclusion, Tanah Para Bandit represents a modern form of patriotism rooted not only in nationalism but also in moral and social consciousness. These values make the novel suitable as literary teaching material for senior high school students, as it fosters a sense of national pride and civic responsibility.